Study on the shear thickening mechanism of multifunctional shear thickening gel and its energy dissipation under impact load. (28th April 2022) - Liu, Bing; Du, Chengbin; Deng, Huaxia; Fu, Yankai; Guo, Fei; Song, Ling; Gong, Xinglong
Abstract: A multifunctional shear thickening gel (MSTG) with both shear thickening performance and magnetorheological effect was prepared by dispersing the carbonyl iron powder into shear stiffening polymer matrix. Upon varying the mass ratio of pyroboric acid to polydimethylsiloxane from 0 to 0.6, the relative shear thickening effect of MSTG first increases and then decreases, demonstrating an excellent shear thickening property between the ratio within 0.2–0.4. A molecular chain model of the cross-linked bond was proposed to illustrate the shear thickening mechanism, and verified by the impact test of MSTG with different proportions. It is believed that more cross-linked bonds were formed at a higher external impact velocity due to the stimuli-response performance of MSTG. Graphical abstract: Image 1 Highlights: Variation rules of ST effect and chain model of MSTG were put forward. The chain model was verified by the impact test of MSTG. An optimization method was proposed to obtain higher shear thickening effect. Energy dissipation values of MSTG at distinct impact velocities were simulated.